Analisis Motor Listrik Tipe Synchronous dengan Metode Komputasi - James Julian; Fitri Wahyuni; Lomo Mula Tua; Nely Toding Bunga (Fakultas Teknik Universitas Pancasila, 2021)
In the current technological development, the electric motor is the most popular in various industrial applications. Electric motors today have evolved very quickly and have a significant impact on the lives of the wider community. The use of environmentally friendly and efficient energy is one of the reasons why this motorbike has become a pioneer of technological advances, especially in the automotive world. This research focuses on conducting a comprehensive analytical study on one type of electric motor, namely synchronous because it is widely applied in various conditions today. The analysis was carried out using a computational method by applying the finite element as a method of solving the magnetic field case involving Maxwell's equations and its impact on the torque generated in this synchronous motor. From the computation results, it is found that this synchronous motor does have a high torque when the magnetic field flux works constantly at 0.015 Wb. With an average torque generated by this synchronous motor of 1.5 kW.